Pengaruh Pemasaran Digital Dan Kualitas Produk Terhadap Keputusan Pembelian Suyo Body Lotion Di Kota Surabaya - Siti Juliana Putri; Iswati Iswati; Anis Fitriysasari (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the effect of digital marketing and product quality on purchasing decisions for Suyo Body Lotion products in Surabaya. The population in this study were all consumers who made purchases of Suyo Body Lotion products. This study uses a quantitative approach. Sampling using a non-probability sampling approach and obtained 65 respondents. The data collection technique was obtained by distributing questionnaires to consumers who buy Suyo Body Lotion products in Surabaya. The data analysis technique uses the Multiple Linear Regression Analysis method. The results showed that, partially (t test) digital marketing has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions. Simultaneous test results (F test) show that digital marketing communication and product quality have a positive and significant effect on purchasing decisions.